Making Peace with Change: The Effect of GPT Chat Utilization on the Performance of Islamic Religion Teachers in Creating Teaching Modules - Syamsul Kurniawan; Saifuddin Herlambang; Nopita Sari; Fikri Fadian; Bayu Suratman; Vibry Andina Nurhidayah; Abdel Kadir Naffati; Torikoh (Yogyakarta: Jurusan Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2024)
Purpose – This study aims to explore the effect of GPT Chat utilization on the performance of Islamic religion teachers in making teaching modules. Specifically, this study examines (1) the performance of Islamic religion teachers before utilizing Chat GPT, (2) how the utilization of Chat GPT by Islamic religion teachers, (3) the performance of Islamic religion teachers after utilizing Chat GPT, and (4) whether there is a significant effect of utilizing Chat GPT on teacher performance in making teaching modules. Design/methods/approach – This research uses a quantitative approach with a pre-experiment design. Data collection tools include questionnaires, observation guidelines, and documentation. Hypothesis testing was conducted through normality tests (Kolmogorov-Smirnov and Shapiro-Wilk) and non-parametric tests (Wilcoxon) to measure significant differences between pretest and posttest results. Findings – The findings of this study indicate that the use of Chat GPT affects the performance of Islamic religion teachers in making teaching modules. Research implications/limitations – This study shows that the utilization of Chat GPT significantly improves teacher performance in doing Islamic religious education teaching modules. However, this study has limitations because of the small sample size of only 22 teachers. Future research can expand the scope by involving a larger sample and other education levels. Originality/value – This study provides empirical evidence of the transformative potential of digital technologies in Islamic religious education practice and offers insights into how teachers can integrate AI technologies to improve Islamic religious education teaching strategies and learning outcomes.